APLIKASI POINT OF SALE PADA RUMAH MAKAN AYAM BAKAR 7 SAUDARA - Franky Wijaya; Ery Dewayani; Manatap Dolok Lauro (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
The Ayam Bakar 7 Saudara restaurant has been established since 1978 and still uses a conventional system in terms of managing its sales. Every month, the number of customers at the restaurant also increases significantly, therefore the risk of mistakes is higher. To overcome this, a Point of Sale application was created which is a software system designed as a cashier which is a point of sale, where the transaction process between buyers and sellers is carried out to completion. This application was created using the OutSystems platform which is a low-code platform that allows the process of making applications faster with minimal typing of programming code. The applied application development method is using the Systems Development Life Cycle (SDLC). The resulting system is divided based on its users, namely Cashier and Admin/Owner. Cashiers can input customer purchases, process payments, and print receipts. Admin/Owner can perform the same functions as the cashier with the addition of product management, view dashboards, print sales reports, manage cashier accounts, view and manage sales history.